Evolución y situación epidemiológica de la infección por virus de inmunodeficiencia humana y síndrome de inmunodeficiencia adquirida en Chile - García O,Maritza (Sociedad Chilena de Infectología, 2008)
In Chile, the first cases of AIDS were reported 23 years ago, and since then, through December 2006, 17.235 persons have been notified with HIV infection or AIDS¹. To the year 2005, there have been 5.288 fatal cases of AIDS. The last available data indicates that notification rates for AIDS and HIV infection in 2006 were 2.5 and 4.5 per 100.000 inhabitants, respectively, and mortality rate for AIDS in 2005 was 2.4 per 100.000 inhabitants. Trend analysis shows a decline in the notification rate among men, both for HIV infection and AIDS, which could be a real decrease or a sub notification bias. In Chile, like in other countries of the region, variations in the epidemiologic pattern were observed considering age group, gender, educational level and geographic distribution of the population. Currently, the Chilean Ministry of Health has implemented both a surveillance and monitoring system on line, in order to improve the quality and opportunity of the information, therefore providing an important tool to HIV infection/AIDS prevention and control strategies